A proteinase-free DNA replication machinery for in vitro and in vivo amplified MicroRNA imaging. Issue 10 (29th April 2020) - Wei, Jie; Wang, Huimin; Gong, Xue; Wang, Qing; Wang, Hong; Zhou, Yangjie; Wang, Fuan
Abstract: The construction of robust, modular and compact DNA machinery facilitates us to build more intelligent and ingenious sensing strategies in complex biological systems. However, the performance of conventional DNA amplifiers is always impeded by their limited in-depth amplifications and miscellaneously enzymatic requirements. Here, a proteinase-free reciprocal DNA replication machinery is developed by exploiting the synergistic cross-activation between hybridization chain reaction (HCR) and DNAzyme. The DNAzyme provides an efficient way to simplify the sophisticated design of HCR machinery and simultaneously to promote the amplification capacity. And the HCR-assembled tandem DNAzyme nanowires produce numerous new triggers for reversely stimulating HCR amplifier as systematically explored by experiments and computer-aided simulations. The reciprocal amplifier can be executed as a versatile and powerful sensing platform for analyzing miRNA in living cells and even in mice, originating from the inherent reaction accelerations and multiple-guaranteed recognitions. The reciprocal catalytic DNA machine holds great potential in clinical diagnosis and assessment.